Carers' Medication Administration Errors in the Domiciliary Setting: A Systematic Review. - Anam Parand; Sara Garfield; Charles Vincent; Bryony Dean Franklin (PLoS ONE)
Purpose Medications are mostly taken in patients' own homes, increasingly administered by carers, yet studies of medication safety have been largely conducted in the hospital setting. We aimed to review studies of how carers cause and/or prevent medication administration errors (MAEs) within the patient's home; to identify types, prevalence and causes of these MAEs and any interventions to prevent them. Methods A narrative systematic review of literature published between 1 Jan 1946 and 23 Sep 2013 was carried out across the databases EMBASE, MEDLINE, PSYCHINFO, COCHRANE and CINAHL. Empirical studies were included where carers were responsible for preventing/causing MAEs in the home and standardised tools used for data extraction and quality assessment. Results Thirty-six papers met the criteria for narrative review, 33 of which included parents caring for children, two predominantly comprised adult children and spouses caring for older parents/partners, and one focused on paid carers mostly looking after older adults. The carer administration error rate ranged from 1.9 to 33% of medications administered and from 12 to 92.7% of carers administering medication. These included dosage errors, omitted administration, wrong medication and wrong time or route of administration. Contributory factors included individual carer factors (e.g. carer age), environmental factors (e.g. storage), medication factors (e.g. number of medicines), prescription communication factors (e.g. comprehensibility of instructions), psychosocial factors (e.g. carer-to-carer communication), and care-recipient factors (e.g. recipient age). The few interventions effective in preventing MAEs involved carer training and tailored equipment. Conclusion This review shows that home medication administration errors made by carers are a potentially serious patient safety issue. Carers made similar errors to those made by professionals in other contexts and a wide variety of contributory factors were identified. The home care setting should be a priority for the development of patient safety interventions.